KONTRIBUSI MUHAMMAD AL-FATIH DALAM MENINGKATKAN ILMU MELALUI PENGEMBANGAN PENDIDIKAN ISLAM DI TURKI - Kumala, Siti Fatmawati; Maslihah, Anis; Rossidy, Imron (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
The purpose of this article is to find out the extent of Sultan Muhammad Al Fatih's contribution in developing science through Islamic education in Turkey, It is reviewed from a historical aspect related to the situation and conditions of education in Turkey during the reign of Sultan Muhammad Al-Fatih which is then described explicitly. The method used in this research is descriptive qualitative, while the data collection process was carried out using the library research. The results of this study indicate that the contribution of Sultan Muhammad Al Fatih in developing science through Islamic education in Turkey can be seen from the efforts to develop academies and schools, Such as the use of the Ayashofiyah and Zayrek mosques as the first Islamic education center in Constantinople (Istanbul, Turkey). then he developed Darul Funun which is now the forerunner of Istanbul University. Apart from that, Muhammad Al-Fatih also built several educational institutions including Miftah school, Kirkha school, Ellili school, Sahn-I school, Altmish school. Hasiye-I Tecrid school, Zeyrek school, Tetimme school, Otuzlu school, Haric Ibtidayah school, Darul hadis school, Darul shifa school, Eyup school, Mektep school.